Prevalence of variant hemoglobins and thalassemias in a maroon community in Sergipe, Brazil - Elizano Santos de Assis; Jamille Alves Araújo; Maria Izabel Ribeiro Cabral de Rezende; Cristiane Costa da Cunha Oliveira; Francisco Prado Reis; Cláudia Moura de Melo (Acta Scientiarum. Health Sciences, 2015)
Current analysis investigates the sickle-cell syndrome among members of a maroon community (comunidade quilombola) in the state of Sergipe, Brazil. The entire population, comprising five hundred and ninety-three people, was screened. Blood samples were collected from 318 people, aged between six months and fifty years, who underwent a solubility test to assess the presence of HbS, followed by Sickle-Cell Test to confirm its presence. Results revealed that 2.2% of the three hundred and eighteen people tested have hemoglobin HbS in their blood; 57% have type HbAS and 43% have a combination between thalassemia and heterozygous with a variable percentage of HbS ranging between 24.9 and 37.9%. Blood sampling revealed that only five out of the 318 people belonged to different families. Results are highly relevant for public health policies on the sickle-cell syndrome and its management.